(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article examines the key factors influencing the economic stability of service sector entities in the context of modern economic development. The relevance of the study is determined by the growing role of the service sector in ensuring sustainable economic growth, employment, and competitiveness. Particular attention is paid to both internal and external factors affecting stability, including financial resilience, management efficiency, market demand, technological innovation, and institutional environment. The study analyzes the impact of macroeconomic conditions, regulatory frameworks, and digital transformation on service sector performance. Methodologically, the research is based on systematic, comparative, and analytical approaches. The interconnection between economic stability and service quality, productivity, and customer satisfaction is highlighted. The findings reveal that effective risk management and adaptive strategies significantly enhance sustainability. The results of the study contribute to the development of practical recommendations aimed at strengthening economic stability. The scientific novelty lies in the integrated assessment of influencing factors. The conclusions may be used by policymakers and business practitioners.